Trancriptome profiles of Amur sturgeon spleen in response to Yersinia ruckeri infection. Issue 70 (November 2017) - Li, Shaowu; Zhang, Ying; Cao, Yongsheng; Wang, Di; Liu, Hongbai; Lu, Tongyan
Abstract: Yersinia ruckeri (YR) is the causative agent of yersiniosis which has caused significant economic losses in fish culture worldwide, including in Amur sturgeon ( Acipenser schrenckii ) culture. To better understand the mechanism of the immune responses to YR in Amur sturgeon, the transcriptomic profiles of the spleens from YR-infected and non-infected groups were obtained using RNA-seq techniques. The de novo assemblies yielded totally 145 670 unigenes from the two libraries. The total numbers of transcripts in YR-infected and non-infected groups were from 110 893 to 147 336, with the mean length varying from 560 to 631 (N50: from 882 to 1083). GO analysis revealed that 10 038 unigenes were categorized into 26 biological processes subcategories, 17 cellular components subcategories and 19 molecular functions subcategories. A total of 59 487 unigenes were annotated in the KEGG pathway and 20 pathways were related to the immune system. 1465 differently expressed genes (DEGs) were identified, including 377 up-regulated genes and 1088 down-regulated genes. 125 DEGs were found to be related to immune responses of Amur sturgeon and further divided into 16 immune-related KEGG pathways, including antigen processing and presentation, complement and coagulation cascades, T cell receptor signaling pathway, B cell receptor signaling pathway, NOD-like receptor signaling pathway, chemokine signaling pathway, etc. Eight of the DEGs were further validated by qRT-PCR. Altogether, the results obtained in this study will provide insight into the immune response of Amur sturgeon against Y. ruckeri infection. Highlights: Transcriptome of Amur sturgeon infected with Yersinia ruckeri was analyzed. Totally 145 670 unigenes were yielded by de novo assembly. Totally 1465 DGEs were identified under Y. ruckeri challenge. 125 DEGs were divided into 16 immune-related KEGG pathways. Eight of DEGs were chosen for further validation using qRT-PCR.